Bullatine A suppresses glioma cell growth by targeting SIRT6 - Zhi Wang; Yushuai Zhu; Can Luo; Fan Zhang; Jiannong Zhao; Chuanyi Fu (Heliyon)
Gliomas are the most common primary tumors of the nervous system, which is generally treated using adjuvant chemotherapy following surgical resection. However, patient survival time is still short, and there is currently no successful treatment for highly malignant gliomas. Bullatine A (BLA) is a diterpenoid alkaloid of the genus Aconitum which antirheumatic and anti-inflammatory pharmacological properties. The effects of BLA on gliomas have not yet been elucidated. In this study, we investigated the effects of BLA on human brain malignant glioblastoma cells. Our results showed that BLA inhibited the proliferation of U87MG and U251 cells in a dose-dependent manner and decreased their survival rate. BLA dose-dependently induced apoptosis in U87MG cells, upregulated the expression of cleaved caspase-9, cleaved caspase-3 pro-apoptotic protein, and Bax protein, and downregulated the expression of Bcl-2 anti-apoptotic protein. Moreover, BLA dose-dependently induced U87MG and U251 cell cycle arrest in the G2/M phase, and downregulated the expression of p-ERK and Myc proteins. Further, BLA significantly inhibited the acetylation of histones H3K9 and H3K56, and upregulated the expression of the protein deacetylase SIRT6. Mechanistic studies revealed that the effect of BLA on inducing apoptosis and inhibiting the proliferation of glioma cells was blocked by SIRT6 knockout. In summary, our study indicated that BLA is a potential therapeutic agent for glioma that targets SIRT6 to inhibit glioma cell proliferation and induce apoptosis.